Analisis Perhitungan Harga Pokok Produksi pada CV. ABC dengan Menggunakan Metode Full Costing - Himawan Pradipta; Audri Selly Kusuma Putri (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
Calculating production costs is more precise and accurate using the full costing method. Therefore, the entire purchasing process includes in detail all costs used in the production process. The purpose of this writing is to identify the production categories used during production as well as understand and compare how costs are paid in calculating production costs with CV ABC and existing theory. The data is used as primary data. Primary data was obtained through work visits and interviews with business owners. The writing results show that in calculating production costs there are differences in total production costs caused by the company's lack of flexibility in grouping production costs so that the calculations do not reflect the correct value.